1993
DOI: 10.1093/jmedent/30.5.943
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Turtles for Mosquito Control in Water Storage Tanks

Abstract: Juvenile turtles, Trachemys scripta, provided highly effective control of mosquito larvae in cement tanks (pilas) where water was stored for household cleaning. When single turtles were introduced to tanks with histories of high mosquito production, nearly all turtles remained in good health and no mosquito larvae survived to the pupal stage. Families welcome turtles in their water storage containers in Honduras. Humane conditions for turtles can be assured by providing small quantities of table scraps to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Both studies utilized an integrated approach in which community members were taught modify their existing practices to maintain copepods in water containers and to dispose of unsuitable water containers. Biological methods of vector control such as copepods and bacteria, were also highly accepted by homeowners (Borjas et al. 1993; Gorrochotegui‐Escalante et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both studies utilized an integrated approach in which community members were taught modify their existing practices to maintain copepods in water containers and to dispose of unsuitable water containers. Biological methods of vector control such as copepods and bacteria, were also highly accepted by homeowners (Borjas et al. 1993; Gorrochotegui‐Escalante et al.…”
Section: Discussionmentioning
confidence: 99%
“…1998). Several authors reported that water was emptied or was subject to seasonal drying; resulting in the death or escape of the organism (Borjas et al. 1993; Gorrochotegui‐Escalante et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some biological control programs have been successful in controlling Ae. aegypti populations (Lima et al 2010, Ghosh et al 2011, Manna et al 2011), but in others, the introduced animals have been potential sources of pathogenic microorganisms (e.g., turtles) (Borjas et al 1993). Community‐based programs are among the most successful mosquito control methods in small rural communities.…”
Section: Introductionmentioning
confidence: 99%